Cloprostenol administration in the first week postpartum reduces expression of oxytocin receptors in the endometrium in Holstein-Zebu cows - Camargos, A.; Wohlres-Viana, S.; Costa, I. F. [UNESP]; Camargo, L. S.; Ferreira, J. C. [UNESP]; Ramos, A. A. [UNESP]; Oba, E. [UNESP] (FapUNIFESP (SciELO), 2017)
The present study investigated the hormonal profile and expression of prostaglandin F2α (PGF2α), oxytocin and estrogen receptors in uterine tissues of postpartum cows treated with cloprostenol. Twenty Holstein- Zebu crossbred cows were treated with saline solution (treatment CONT) or cloprostenol (treatment CLO), both administered two and five days postpartum. Blood samples were collected on days two, seven, 14, 21 and 28 postpartum for progesterone, PGF2α metabolite (PGFM) and estradiol determination, and endometrial biopsy was performed in order to quantify the expression of oxytocin receptor (OXTR), prostaglandin F receptor (PTGFR) and estrogen receptor 1 (ERS1) genes. In the CLO treatment, expression of OXTR was reduced (P < 0.05) but no difference (P > 0.05) between treatments was found for PTGFR and ERS1 expression. Estrogen concentrations increased progressively until day 14 (P < 0.05) and the highest OXTR expression and lowest PTGFR expression were observed on day 14 (P < 0.05) in both treatments. Serum PGFM concentrations were high throughout the experiment. In conclusion, cloprostenol administration at days two and five of postpartum seems to reduce OXTR expression in the endometrium in crossbred cows.
Keywords: ESR1; Estradiol; Progesterone; PTGFR; RT-PCR